Original articleUltrastructural study of cerebellar dentate nucleus astrocytes in chronic experimental model with valproate - Sobaniec-Łotowska, Maria E.; Łotowska, Joanna M. (Folia Neuropathologica, 2005)
The current study focuses on the morphogenesis of changes in the cerebellum dentate nucleus in the course of experimental valproate encephalopathy. Valproate – a broad spectrum antiepileptic and antipsychotic drug – chronically used in rats, intragastrically, once daily at a dose of 200 mg/kg b. w. for 1, 3, 6, 9 and 12 months, induced pronounced ultrastructural changes in the population of glial cells and nerve cells of the dentate nucleus of the cerebellum in the last two phases of the experiment. Astrocytic and neuronal lesions coexisted with a considerable damage to the elements of the blood-brain barrier of the cerebellar structure examined. The changes affected mainly the population of protoplasmic astrocytes lying loosely in a neuropile as well as astrocytes adhering to damaged large multipolar neurons. Focal proliferation of astrocytes was observed. Abnormal astrocytes showed marked swelling expressed by significantly decreased electron density of the cytoplasm that contained almost empty vacuolar structures and by a considerably reduced number of intracellular organelles. It was accompanied by dilation of endoplasmic reticular channels, loss of fibrillopoietic capacity of the cell and features of autophagocytosis. It should be assumed that the essential cause of protoplasmic astroglial damage of the cerebellar dentate nucleus could be associated, apart from the direct effect of valproate and/or its metabolites on these cells, with changes in structural elements of the blood-brain barrier of this CNS region.